Pengaruh Pendidikan Kesehatan Terhadap Keterampilan Ibu PKK Dalam Melakukan SADARI - Rosyida, Ananda Dwi; Mustafa, Annasari; Yulifah, Rita; Triningsih, Reni Wahyu (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2025)
Breast cancer is one of the leading causes of death among women in Indonesia. One simple and self-administered method of early detection is Breast Self-Examination (SADARI). However, women’s skills in performing SADARI remain relatively low, including among PKK mothers, who play a strategic role in community health education. This low level of skill is caused by lack of information, minimal hands-on practice, and the absence of ongoing training. Health education is one intervention believed to improve these skills. This study aimed to determine the effect of health education on the skills of PKK mothers in performing SADARI in Rampal Celaket Subdistrict, Malang City. The research used a pre-experimental design with a one-group pretest-posttest approach. A total of 35 respondents were selected through purposive sampling. Data were collected using an observation checklist for SADARI skills covering 20 indicators. Data analysis was performed using the Wilcoxon Signed Rank Test. The results showed a significant improvement in skills after the health education intervention, with a p-value < 0.05. Before the intervention, most respondents were only able to perform around 6–7 out of 20 SADARI steps, whereas after the intervention, the majority were able to perform all 20 steps correctly and sequentially. It can be concluded that health education significantly improves the skills of PKK mothers in performing SADARI. Therefore, a structured and sustainable health education program should be considered as a promotive strategy to encourage early detection of breast cancer in the community.